Mechanical Properties of Hybrid Kenaf - Pineapple Leaf Fibre (PALF) Epoxy Composite For Engineering Application - Mohd Abdul Rahman, Muhammad Zuhair; Ariffin, Ahmad Hamdan (Progress in Aerospace and Aviation Technology, 2022)
Natural fibres nowadays been famously investigated as alternative fibres due to the source depletion of petroleum. There are several natural fibres such as jute, hemp, sisal, kenaf and pineapple leaf that been actively researched in terms of their mechanical properties. This research was focusing on two of the natural fibres which are the kenaf and pineapple leaf. The kenaf and pineapple leaf fibres were proved by previous researchers to have good mechanical properties. This study aims to test the hybrid of Hybrid Kenaf and Pineapple leaf Fibre (PALF) epoxy composite for engineering application. The mechanical properties of hybrid pineapple leaves and kenaf fibre composite will be investigated. The tensile test will be performed in mechanical properties analysis. This research conducted to ensure that the fibre is being utilized rather than being left out as waste, especially by the agriculture industries and the data of the mechanical properties of pineapple leaves and kenaf fibre composite can be obtained through tests conducted. The test result found that this hybrid can perform better than the existing natural fibre hybrid. Hybridization of pineapple leaf fibre and kenaf fibre has higher maximum stress using composition of 75 pineapple leaf fibre to 25 kenaf fibre percentage which is 87.06 MPa.